Lysyl Oxidase Family Proteins: Prospective Therapeutic Targets in Cancer - Wei Wang; Xiangjun Wang; Feng Yao; Chao Huang (2022)
The lysyl oxidase (LOX) family, consisting of LOX and LOX-like proteins 1–4 (LOXL1–4), is responsible for the covalent crosslinking of collagen and elastin, thus maintaining the stability of the extracellular matrix (ECM) and functioning in maintaining connective tissue function, embryonic development, and wound healing. Recent studies have found the aberrant expression or activity of the LOX family occurs in various types of cancer. It has been proved that the LOX family mainly performs tumor microenvironment (TME) remodeling function and is extensively involved in tumor invasion and metastasis, immunomodulation, proliferation, apoptosis, etc. With relevant translational research in progress, the LOX family is expected to be an effective target for tumor therapy. Here, we review the research progress of the LOX family in tumor progression and therapy to provide novel insights for future exploration of relevant tumor mechanism and new therapeutic targets.